EXPLORING THE THERAPEUTIC POTENTIAL OF AM114: A BORONIC CHALCONE DERIVATIVE INDUCE APOPTOSIS AND SUPPRESS PROINFLAMMATORY CYTOKINES AND CHEMOKINES IN INTERLEUKIN-1β STIMULATED HUMAN THP-1 DERIVED MACROPHAGES - SELVARAJAN, CHITRA; GANESAN, NALINI (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: Chalcones and their derivatives display a wide range of pharmacological activities. This study examined the effects of AM114, a boronic-chalcone derivative, on human THP-1-derived macrophages with and without interleukin-1β (IL-1β) stimulation. Methods: AM114 and Aspirin-treated THP-1-derived macrophages underwent activation with or without interleukin-1β. The IC50 concentrations of AM114 and Aspirin were determined through an MTT test. Apoptosis was measured using various techniques, including staining with acridine orange/Ethidium bromide, Hoechst 33342, and rhodamine 123 assays. Caspase-3 activity was measured using the spectrofluorimetric technique, while DNA fragmentation was assessed via agarose gel electrophoresis. Pro-inflammatory cytokines such as interleukin-6 (IL-6) and chemokines like interleukin-8 (IL-8) were measured using enzyme-linked immunosorbent assays. Results: AM114 and Aspirin showed dose-dependent cytotoxic effects on THP-1 macrophages. Induction of apoptosis was detected in AM114-treated THP-1 macrophages activated with IL-1β compared to macrophages without IL-1β. The gradation of dye uptake, membrane blebbing, increased caspase-3 activity, and DNA fragmentation ensures the induction of apoptosis, which indicates the cell's morphological changes, biochemical processes, and mitochondrial activity. Treating AM114 in IL-1β-activated THP-1 macrophages significantly reduced pro-inflammatory cytokines (IL-6) and chemokines (IL-8), suggesting its anti-cytokine potential in inflammatory diseases. Conclusion: The study results emphasize that AM114 could act as an anti-inflammatory agent by triggering apoptosis and reducing the release of cytokines and chemokines in inflammatory conditions. As a result, it may be used as a therapeutic option for inflammatory diseases.